Effect of agar concentration in culture medium on in vitro development of potato plants (Research, Society and Development, 2020)
In vitro propagation and tissue culture technique is an alternative for obtaining healthy potato seeds. However, data found in the literature differ on the optimal consistency of the culture medium to be used in vitro. The aim in this research was to look at the adaptation of potato cultivars to medium with different agar concentrations. The experimental design was entirely randomized in a factorial scheme. The experiment tested the effect of 3 agar medium concentrations (solid, semisolid and liquid) on 6 cultivars (Agata, Bel, Camila, Catucha, Clara and Eliza), with 5 repetitions. We quantified from the plantlets, fresh and dry mass of roots and shoot, the number of nodes, the multiplication capacity and vigor. The study showed that potato cultivars respond significantly to different concentrations of agar and their best response was in the semisolid medium.